2021
DOI: 10.54055/ejtr.v30i.2169
|View full text |Cite
|
Sign up to set email alerts
|

The impact of advertising creativity on purchase intention in the airline industry: A stimulus-organism-response (S-O-R) perspective

Abstract: This study aims to understand the impact of advertising creativity on purchase intention in the airline industry. To this end, drawing on the Stimulus-Organism-Response (S-O-R) framework, the associations among advertising creativity, attitude toward advertising, flow experience, and purchase intention were investigated. Utilizing a total sample of 174 respondents in Turkey, the partial least squares structural equation modeling (PLS-SEM) approach was adopted to testing the research model. The results suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…The consumer response of learning and remembering ad claims refer to the ads associating brands with positively valued traits. As brands are more associated with positive traits as evaluated by consumers, the more favorably disposed the consumers will be toward purchase [ 35 , 18 ]. Emotions influence the selectivity of attention, motivating action and behavior, facilitating encoding and retrieval of information [ 40 ] and providing a conducive context to learning and retention of information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consumer response of learning and remembering ad claims refer to the ads associating brands with positively valued traits. As brands are more associated with positive traits as evaluated by consumers, the more favorably disposed the consumers will be toward purchase [ 35 , 18 ]. Emotions influence the selectivity of attention, motivating action and behavior, facilitating encoding and retrieval of information [ 40 ] and providing a conducive context to learning and retention of information.…”
Section: Discussionmentioning
confidence: 99%
“…This final stage of the HOE refers to the intent to recommend or intent to purchase the advertised brand and is highly dependent on the prior stages working as a funnel to take effect. Creative ads also produce high levels of liking and purchase interest, positively affecting brand attitudes and purchase intentions [ 19 , 20 , 35 ]. AC has been argued to signal product quality among consumers affecting quality perceptions and influencing brand intention [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scholars widely use SOR in the retail studies for traditional shopping experience reviews as a review tool for consumers' purchase decision-making processes and consumer behavior (Othman et al, 2016;Bigne et al, 2019;Jeong et al, 2020). Researchers use SOR theory to evaluate consumers' online shopping behavior (Zimmerman 2017;Bigne et al, 2019;Sarılgan et al, 2022;Talwar et al, 2022). Researchers use SOR theory to assess consumers' online shopping behavior.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the Stimuli-Organism-Response theory is widely used in retail studies for traditional shopping experience reviews as a review tool for consumers' purchase decision-making processes and behavior (Othman et al, 2016;Bigne et al, 2019;Jeong et al, 2020). It is also extensively used in online shopping behavior and how people are driven for online purchases using various variables and moderators with a prime focus on the convenience of online shopping and the ease of use of those websites (Zimmerman 2017;Bigne et al, 2019;Sarılgan et al, 2022;Talwar et al, 2022). The flexibility of this theory and its ability to obtain various variables-often used in different supporting theories-is the reason for choosing it as the grounding theory in this study.…”
Section: Stimulus Organism Responsementioning
confidence: 99%
“…For example, Lange et al (2016) confirmed that creative window is an important driver of customer visit behavior [2]. Sılgan et al (2022) empirically found that creative advertising has a positive impact on product purchase intention based on S-O-R theory [3]. In addition, studies of other scholars also show that website creativity has a positive impact on tourists' offline travel intention (Cai et al [4], 2017).…”
Section: Introductionmentioning
confidence: 87%